Carbonate Apatite Nanoparticles-Facilitated Intracellular Delivery of siRNA(s) Targeting Calcium Ion Channels Efficiently Kills Breast Cancer Cells - Uddin, Mohammad Borhan (Toxics, 2018)
Specific gene knockdown facilitated by short interfering RNA (siRNA) is a potential approach for suppressing the expression of ion channels and transporter proteins to kill breast cancer cells. The overexpression of calcium ion channels and transporter genes is seen in the MCF-7 breast cancer cell line. Since naked siRNA is anionic and prone to nuclease-mediated degradation, it has limited permeability across the cationic cell membrane and short systemic half-life, respectively. Carbonate apatite (CA) nanoparticles were formulated, characterized, loaded with a series of siRNAs, and delivered into MCF-7 and 4T1 breast cancer cells to selectively knockdown the respective calcium and magnesium ion channels and transporters. Individual knockdown of TRPC6, TRPM7, TRPM8, SLC41A1, SLC41A2, ORAI1, ORAI3, and ATP2C1 genes showed significant reduction (p < 0.001) in cell viability depending on the cancer cell type. From a variety of combinations of siRNAs, the combination of TRPC6, TRPM8, SLC41A2, and MAGT1 siRNAs delivered via CA produced the greatest cell viability reduction, resulting in a cytotoxicity effect of 57.06 ± 3.72% (p < 0.05) and 59.83 ± 2.309% (p = 0.09) in 4T1 and MCF-7 cell lines, respectively. Some of the combinations were shown to suppress the Akt pathway in Western Blot analysis when compared to the controls. Therefore, CA-siRNA-facilitated gene knockdown in vitro holds a high prospect for deregulating cell proliferation and survival pathways through the modulation of Ca(2+) signaling in breast cancer cells.